HUBUNGAN ANTARA PENYESUAIAN DIRI DENGAN CULTURE SHOCK PADA MAHASISWA NUSA TENGGARA TIMUR (NTT) SEMESTER PERTAMA DI UNIVERSITAS WIJAYA PUTRA SURABAYA - Bergitha Dhei; Fitriana Fatmawati S; Angga Dani Prasetia; Ardianti Agustin (PSIKOWIPA (Psikologi Wijaya Putra), 2020)
Culture shock is a condition that can cause confusion to the environment with a new culture so that it can triggernegative emotions. Adjustment is a process that includes mental response and behavior, individuals trying to beable to successfully overcome the needs in themselves, tensions, conflicts and frustration they experience, so as torealize the level of harmony between demands from within with what expected by the environment. This studyaims to determine the relationship between adjustment and culture shock in NTT students in the early semester atWijaya Putra University. The hypothesis in this study is that there is a significant relationship between selfadjustment and culture shock. The number of samples used is 50 respondents. The sampling technique used in thisstudy was purposive incidental sampling. Measuring instruments used were culture shock scale questionnaire 32items and adjustment items scale 59 items. Data were analyzed using product moment analysis. The analysisshows the value (rxy) = -0.652 with p = 0.000 (p <0.05), meaning that there is a negative relationship betweenadjustment and culture shock ie the lower the level of adjustment, the higher the level of culture shock in NTTstudents in the early semester in Wijaya Putra University.